Efektivitas Mckenzie dan Kegel Exercise terhadap Penurunan Nyeri Dismenore pada Remaja Usia 12 – 15 Tahun di SMP Negeri 28 Semarang - Andryani Mutiara; Syurrahmi Syurrahmi; Wibisono SL; Najizah Fitratun (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Dysmenorrhea is a painful cramping or aching sensation in the lower abdomen, often radiating to the lower back, hips, and thighs. This condition significantly affects daily activities, limiting women’s physical and academic performance, particularly among female students who frequently experience dysmenorrhea during menstruation. Various interventions can help prevent or reduce the prevalence and severity of dysmenorrhea, including specific physical exercises such as McKenzie exercises and Kegel exercises. McKenzie exercises focus on strengthening and mobilizing the lower back and abdominal muscles, whereas Kegel exercises target the pelvic floor muscles to enhance circulation and reduce uterine tension. The purpose of this study was to determine the difference in effectiveness between Kegel exercises and McKenzie exercises in alleviating dysmenorrhea pain among adolescents aged 12–15 years at SMP Negeri 28 Semarang. The study employed an experimental two-group pre-posttest design with a total sample of 22 female students who met the inclusion criteria. The Randomized Controlled Trial (RCT) technique was used to assign participants to the intervention groups. Pain intensity was measured using the Quadruple Visual Analog Scale (QVAS) both before and after the interventions, which were administered three times per week over a three-week period. The results showed a statistically significant reduction in pain for both groups, with a p-value of 0.001 (p < 0.05), indicating that both McKenzie and Kegel exercises effectively decreased dysmenorrhea pain. The study concluded that there is a measurable difference in the effectiveness of these two exercise interventions, emphasizing the importance of selecting appropriate physical exercises tailored to adolescent students for dysmenorrhea management. These findings provide evidence-based guidance for educators, healthcare providers, and adolescents seeking non-pharmacological strategies to reduce menstrual pain and improve quality of life.